Introduction to quantitative EEG and neurofeedback : advanced theory and applications - Budzynski, Thomas H.; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier ; Burlington, MA : Academic Press, 2009)
The study of quantitative EEGs and neurofeedback offers a window into brain physiology and function via computer and statistical analyses, suggesting innovative approaches to the improvement of attention, anxiety, mood and behavior. Resources for understanding what QEEG and Neurofeedback is, how they are used, and to what disorders and patients they can be applied are scarce, and this volume serves as an ideal tool for clinical researchers and practicing clinicians, providing a broad overview of the most interesting topics relating to the techniques. The revised coverage of advancements, new applications (e.g. Aspberger's, music therapy, LORETA, etc.), and combinations of prior approaches make the second edition a necessary companion to the first. The top scholars in the field have been enlisted and contributions will offer both the breadth needed for an introductory scholar and the depth desired by a clinical professional. *Detailed new protocols for treatment of anxiety, depression, ADHD, and newest protocol in Z-score training enables clinicians to extend their practices. LORETA diagnostic tool lets the clinician watch for changes deep in the brain through working with surface EEG patterns.
pt. 1. QEEG and neurofeedback: basics and new theory. Neuromodulation technologies: an attempt at classification / Siegfried Othmer ; History of the scientific standards of QEEG normative databases / Robert W. Thatcher and Joel F. Lubar -- pt. 2. Advancing neurofeedback practice. Applying advances methods in clinical practice / David S. Cantor ; Diagnosing and treating brain function through the use of low resolution brain electromagnetic tomography (LORETA) / Leslie H. Sherlin ; EEG biofeedback training using live Z-scores and a normative database / Thomas F. Collura [and others] ; Alpha-theta neurotherapy and the neurobehavioral treatment of addictions, mood disorders and trauma / Nancy E. White and Leonard M. Richards -- pt. 3. Alternative treatment approaches to neurofeedback. Hemoencephalography: photon-based blood flow neurofeedback / Hershel Toomim and Jeffrey Carmen ; Audio-visual entertainment in relation to mental health and EEG / Thomas F. Collura and David Siever ; Brain music treatment: a brain/music interface / Galina Mindlin and James R. Evans -- pt. 4. Recent clinical applications of neurofeedback. Neurofeedback in alcohol and drug dependency / David L. Trudeau, Tato M. Sokhadze, and Rex L. Cannon ; EEG evaluation of traumatic brain injury and EEG biofeedback treatment / Robert W. Thatcher ; Neurofeedback for the treatment of depression: current status of theoretical issues and clinical research / D. Corydon Hammond and Elsa Baehr ; Neurofeedback and attachment disorder: theory and practice / Sebern F. Fisher ; QEEG and neurofeedback for assessment and effective intervention with attention deficit hyperactivity disorder (ADHD) / Lynda Thompson and Michael Thompson ; Asperger's syndrome intervention: combining neurofeedback, biofeedback and metacognition / Michael Thompson and Lynda Thompson ; Neurofeedback in pain management / Victoria L. Ibric and Livia G. Dragomirescu ; Anxiety, EEG patterns and neurofeedback / Jane Price and Thomas Budzynski -- pt. 5. Ethical/legal issues. Ethics in neurofeedback practice / Sebastian Striefel.
Previous edition: 1999.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Electroencephalography; HEALTH & FITNESS -- Diseases -- Nervous System (incl. Brain); MEDICAL -- Neurology; Electroencephalography; Biofeedback; Elektro-encefalografie.; Electronic books